Graduated driver license compliant teens involved in fatal motor vehicle crashes. (September 2015) - Pressley, Joyce C.; Addison, Diane; Dawson, Patrick; Nelson, Sharifa S.
Abstract : BACKGROUND: Significant reductions in motor vehicle injury mortality have been reported for teen drivers after passage of graduated driver licensing (GDL), seat belt, and no tolerance alcohol and drug laws. Despite this, teen drivers remain a vulnerable population with elevated fatal crash involvement. This study examines driver, vehicle, and crash characteristics of GDL-compliant, belted, and unimpaired teen drivers with the goal of identifying areas where further improvements might be realized. METHODS: The Fatality Analysis Reporting System (FARS) for 2007 to 2009 was used to examine and classify driver violations/errors in compliant teen drivers (n = 1, 571) of passenger vehicles involved in a fatal collision. Teens driving unbelted, non–GDL compliant, or impaired by alcohol or drugs were excluded. Statistical analysis used χ 2, Fisher's exact and multivariable logistic regression. Odds ratios are reported with 95% confidence intervals. Significance was defined as p < 0.05. RESULTS: Nearly one third (n = 1, 571) of teen drivers involved in a fatal motor vehicle crash were GDL compliant, unimpaired, and belted. The majority held an intermediate GDL license (90.6%). Crash-related factors were identified for 63.1% of fatal crashes. Age- and sex-adjusted odds identified overcorrecting, speeding, lane errors, school morning crashes, distractions, and driving on slippery surfaces as having increased odds of fatality for the teen driver as well as newer vehicle models and heavier vehicle weight as protective. CONCLUSION: Among compliant drivers, weekday crashes before and after school and committing a driving violation at the time of crash were associated with increased risk of driver death and higher incidence of incapacitating injury in surviving drivers. LEVEL OF EVIDENCE: Therapeutic study, level V.